A flat-plate solar collector thermal insulation material and preparation method thereof

By using microcapsule wall materials and light stabilizers combined with polyether diol and starch in phenolic foam insulation materials, combined with nanotitanium dioxide, the problem of aging of phenolic foam under oxidation and ultraviolet light is solved, and the solar thermal collection of flat panels is significantly improved Anti-aging properties of the insulating material of the instrument.

CN119019808BActive Publication Date: 2025-01-07TIANJIN JINJIU NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411507539.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-07
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

Phenolic foam insulation materials tend to age under long-term oxidation, moisture, ultraviolet rays and other environments, resulting in a decrease in insulation effect and have a great impact on the thermal efficiency of flat-panel solar heat collectors.

Method used

Polyether diol and starch are mixed as microcapsule wall material to wrap anti-aging agent, combined with benyl diformyl ultraviolet absorber and hindered amine light stabilizer, and added to phenolic resin through microencapsulation treatment to form a dense protection The membrane delays the aging process and improves the surface roughness and anti-aging ability of microcapsules through nanotitanium dioxide.

Benefits of technology

The aging process of insulation materials has been significantly delayed. The tensile strength and fracture strength retention rates after ultraviolet aging reach 97.2-99.9% and 95.9-99.8%, respectively, greatly improving the anti-aging performance of insulation materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the technical field of thermal insulation materials, in particular to a thermal insulation material for a flat solar collector and a preparation method thereof. The thermal insulation material for a flat solar collector comprises 100-150 parts of phenolic resin, 10-15 parts of a foaming agent, 20-25 parts of a curing agent, 5-8 parts of a stabilizer, and 4-8 parts of a microencapsulated anti-aging agent; the microencapsulated anti-aging agent is prepared by mixing polyether diols and starch as wall materials and using the anti-aging agent as a core material. The preparation method is as follows: phenolic resin, foaming agent, stabilizer, and microencapsulated anti-aging agent are mixed according to a ratio; a curing agent is added; the temperature is raised to 50-70°C for pre-foaming for 30-40 minutes; foaming and curing at 90-100°C for 1-2 hours, cooling, and demoulding. After 15 days of ultraviolet aging treatment, the obtained thermal insulation material can achieve a tensile strength aging retention rate of 97.2-99.9%, and a breaking strength retention rate of 95.9-99.8%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of thermal insulation materials, and in particular to a thermal insulation material for a flat-plate solar collector and a preparation method thereof. Background Art

[0002] Flat-plate solar collectors are the basic components for low-temperature solar thermal utilization. They are non-concentrating components in solar thermal utilization systems that receive solar radiation and transfer heat to the heat transfer medium. Flat-plate solar collectors are mainly composed of a heat absorbing plate, a transparent cover, a heat insulation layer, and a shell.

[0003] The role of the insulation layer is to reduce the heat dissipation of the collector to the surrounding environment, so as to improve the thermal efficiency of the collector. Phenolic foam is a commonly used insulation material. Phenolic foam is a closed-cell rigid foam plastic made of phenolic resin and flame retardants, smoke suppressants, curing agents, foaming agents, and other additives through a scientific formula.

[0004] Phenolic foam insulation materials have been widely used and recognized in construction and other fields due to their light weight, fire resistance, high and low temperature resistance, good thermal insulation, water resistance and water vapor permeability, corrosion resistance, and environmental protection. However, phenolic foam insulation materials are prone to aging and cracking under long-term oxidation, moisture, ultraviolet rays, etc., resulting in a decrease in insulation effect, which has a great impact on the effect of flat-plate solar collectors. Summary of the invention

[0005] In order to improve the anti-aging effect of a flat-plate solar thermal collector insulation material, the present application provides a flat-plate solar thermal collector insulation material and a preparation method thereof.

[0006] In a first aspect, the present application provides a flat-plate solar collector insulation material, which adopts the following technical solution.

[0007] A flat-plate solar collector insulation material comprises the following raw materials in parts by weight: 100-150 parts of phenolic resin, 10-15 parts of foaming agent, 20-25 parts of curing agent, 5-8 parts of stabilizer, and 4-8 parts of microencapsulated anti-aging agent;

[0008] The microencapsulated anti-aging agent is prepared by mixing polyether diol and starch as wall materials and using the anti-aging agent as core material.

[0009] By adopting the above technical scheme, polyether diol and starch are mixed as wall materials to encapsulate the anti-aging agent to prepare microencapsulated anti-aging agent and add it into the thermal insulation material.

[0010] Starch and polyether diol are compounded as wall materials, tightly including the anti-aging agent to form a dense protective film, so that the anti-aging agent is continuously dispersed in the phenolic resin matrix, continuously exerting the anti-aging effect and delaying the aging of the thermal insulation material.

[0011] Furthermore, the weight ratio of polyether diol to starch in the wall material is (5-8):1.

[0012] By adopting the above technical scheme, polyether diol and starch are compounded as wall materials. Starch has good processing performance and certain hygroscopicity and moisture retention, which can slow down the water absorption of the anti-aging agent as the core material and reduce the probability of failure of the anti-aging agent due to water absorption. However, the flexibility of starch as a wall material is poor. Polyether diol has a long and soft molecular chain, so the microcapsule wall material prepared therefrom has high flexibility and can adapt to core materials of various shapes and sizes, which is conducive to protecting the integrity and stability of the core material and making up for the poor flexibility of starch wall materials. At the same time, starch can also make up for the shortcomings of low viscosity and poor moldability of polyether diol. The two are matched, and the prepared microencapsulated anti-aging agent has excellent overall performance, so that the anti-aging agent is continuously released and the anti-aging performance of the thermal insulation material is improved.

[0013] Furthermore, the anti-aging agent is a benzoyl diformyl ultraviolet absorber and a hindered amine light stabilizer in a weight ratio of 1:(2-4).

[0014] By adopting the above technical scheme, the benzoyl diformyl ultraviolet absorber and the hindered amine light stabilizer are released into the thermal insulation material. When ultraviolet rays are irradiated to the surface of the thermal insulation material, the benzoyl diformyl ultraviolet absorber can capture these high-energy ultraviolet photons. After absorbing ultraviolet rays, the absorber will undergo a series of physical and chemical changes, converting the absorbed energy into heat energy or releasing it in the form of harmless low-energy radiation. These processes consume the energy of ultraviolet rays, thereby avoiding direct damage to the material by ultraviolet rays. When ultraviolet rays are irradiated to the surface of the thermal insulation material, free radicals are generated inside the polymer material. These free radicals are very active and can trigger chain reactions, leading to polymer degradation and aging. Functional groups such as amino groups in the hindered amine light stabilizer can capture these free radicals and react with them to form stable compounds, thereby effectively preventing the chain reaction initiated by free radicals and protecting the polymer material from damage. The hindered amine light stabilizer can also protect the polymer material by adjusting the rate of photo-oxidation or thermal oxidation reactions. Under the action of light and oxygen, polymer materials are prone to photo-oxidation and thermal oxidation reactions, leading to chain breakage and degradation. Hindered amine light stabilizers can react with excited free radicals, slowing down or preventing their further reaction with oxygen, thereby reducing the oxidation rate of polymer materials. The synergistic effect of the two greatly delays the aging of thermal insulation materials.

[0015] Furthermore, the preparation method of the microencapsulated anti-aging agent is:

[0016] 1) Heat the antioxidant to a molten state;

[0017] 2) Dissolve starch in water, heat and stir to form a uniform starch solution;

[0018] 3) Add the molten antioxidant and polyether diol to the starch solution, then add the emulsifier, and disperse by shearing to form a stable emulsion;

[0019] 4) Add curing agent to the emulsion to react and complete the microencapsulation process;

[0020] 5) After the microencapsulation reaction is completed, the unreacted raw materials and solvent are removed through the steps of centrifugation, washing and drying to obtain a microencapsulated anti-aging agent.

[0021] Furthermore, the particle size of the emulsion is 500-700 μm.

[0022] Furthermore, the wall material also includes nano titanium dioxide, which is dispersed in the starch solution.

[0023] Furthermore, the weight ratio of the nano titanium dioxide to starch is 1:(2-4).

[0024] By adopting the above technical solution, nano titanium dioxide is embedded in the wall material, which, on the one hand, improves the surface roughness of the microcapsules and improves the bonding ability between the microcapsules and the matrix; on the other hand, nano titanium dioxide also has an anti-aging effect, so that the microcapsule wall material also has a certain anti-aging ability, further improving the anti-aging performance of the thermal insulation material.

[0025] Furthermore, the phenolic resin is a lignin-modified phenolic resin.

[0026] Furthermore, the preparation method of the lignin modified phenolic resin is:

[0027] a) Degradation of lignin by microwave digestion;

[0028] b) melting phenol;

[0029] c) mixing the degraded lignin with melted phenol at a weight ratio of 2:(3-5) to obtain a mixed solution;

[0030] d) adding formaldehyde to the mixed solution in batches and reacting at 60-80°C;

[0031] e) After the reaction is completed, the water is removed by rotary evaporation to obtain pure phenolic resin.

[0032] In a second aspect, the present application provides a method for preparing a flat-plate solar collector insulation material, which adopts the following technical solution.

[0033] A method for preparing a flat-plate solar collector insulation material comprises the following steps:

[0034] S1. The phenolic resin, the blowing agent, the stabilizer and the microencapsulated anti-aging agent are mixed according to the ratio to obtain a mixture;

[0035] S2. adding a curing agent to the mixture and mixing to obtain a reaction system;

[0036] S3. The reaction system is heated to 50-70°C for pre-foaming for 30-40 minutes;

[0037] S4. After pre-foaming, pour it into a preheated mold, foam and cure it at 90-100°C for 1-2 hours, then cool and demould to obtain a flat-plate solar collector insulation material.

[0038] In summary, this application has the following beneficial effects:

[0039] Starch and polyether diol are compounded as wall materials, tightly included in the anti-aging agent to form a dense protective film, and a microencapsulated anti-aging agent is obtained. The microencapsulated anti-aging agent is added to the thermal insulation material, so that the anti-aging agent is continuously dispersed in the phenolic resin matrix, continuously exerting the anti-aging effect, and delaying the aging of the thermal insulation material. After 15 days of ultraviolet aging treatment, the obtained thermal insulation material can achieve a tensile strength aging retention rate of 97.2-99.9%, and a breaking strength retention rate of 95.9-99.8%. DETAILED DESCRIPTION

[0040] The present application is further described in detail below with reference to the embodiments.

[0041] Raw materials and intermediate preparation examples

[0042] raw material

[0043] The raw materials in the examples of this application can be obtained from the market:

[0044] Blowing agent, pentane;

[0045] Curing agent, benzenesulfonic acid;

[0046] Stabilizer, polyvinyl alcohol;

[0047] Alkali lignin, technical grade;

[0048] Phenol, analytical grade;

[0049] Formaldehyde, analytical grade.

[0050] Preparation Example

[0051] Preparation Example 1

[0052] A lignin-modified phenolic resin, the preparation method of which is as follows:

[0053] a) Degrading lignin in a microwave digester at a temperature of 170°C and a degradation time of 15 minutes;

[0054] b) heating phenol until it melts to obtain a phenol solution;

[0055] c) mixing 2 kg of degraded lignin with 4 kg of melted phenol to obtain a mixed solution;

[0056] d) Add 0.5 kg of formaldehyde to the mixture, react at 60°C for 1 hour, then add 0.8 kg of formaldehyde and continue to react at 80°C for 1.5 hours;

[0057] e) After the reaction is completed, the water is removed by rotary evaporation to obtain pure phenolic resin.

[0058] Preparation Example 2

[0059] Different from Preparation Example 1, in Preparation Example 2, c) 2 kg of degraded lignin was mixed with 3 kg of melted phenol to obtain a mixed solution; d) 0.4 kg of formaldehyde was added to the mixed solution, reacted at 60° C. for 1 hour, and then 0.6 kg of formaldehyde was added, and the reaction was continued at 80° C. for 1.5 hours.

[0060] Preparation Example 3

[0061] The difference from Preparation Example 3 is that in Preparation Example 3, c) 2 kg of degraded lignin is mixed with 5 kg of melted phenol to obtain a mixed solution; d) 0.6 kg of formaldehyde is added to the mixed solution, reacted at 60° C. for 1 hour, and then 0.9 kg of formaldehyde is added, and the reaction is continued at 80° C. for 1.5 hours.

[0062] Preparation Example 4

[0063] A microencapsulated anti-aging agent, the preparation method of which is as follows:

[0064] 1) Heat 15 kg of antioxidant to a molten state; the antioxidant is a benzoyl diformyl ultraviolet absorber and a hindered amine light stabilizer in a weight ratio of 1:2;

[0065] 2) Dissolve 3 kg of starch in water, heat and stir to form a uniform starch solution with a concentration of 15% w / v;

[0066] 3) Add the molten antioxidant and 15 kg of polyether diol to the starch solution, then add 0.5 kg of emulsifier, and disperse by shearing to form a stable emulsion with a droplet size of 600 μm;

[0067] 4) Add 0.2 kg of amine compound curing agent into the emulsion to react and complete the microencapsulation process;

[0068] 5) After the microencapsulation reaction is completed, the unreacted raw materials and solvent are removed through the steps of centrifugation, washing and drying to obtain a microencapsulated anti-aging agent.

[0069] Preparation Example 5

[0070] The difference from Preparation Example 4 is that in Preparation Example 5, the amount of starch is 2 kg and the amount of polyether diol is 16 kg.

[0071] Preparation Example 6

[0072] The difference from Preparation Example 4 is that in Preparation Example 6, the amount of starch is 4 kg and the amount of polyether diol is 14 kg.

[0073] Preparation Example 7

[0074] A microencapsulated anti-aging agent, the preparation method of which is as follows:

[0075] 1) Heat 15kg of antioxidant to a molten state; the antioxidant is a benzoyl diformyl UV absorber and a hindered amine light stabilizer in a weight ratio of 1:2.

[0076] 2) Dissolve 18 kg of starch in water, heat and stir to form a uniform starch solution with a concentration of 15% w / v;

[0077] 3) Add the molten antioxidant to the starch solution, then add 0.5 kg of the cross-linking agent to react and complete the microencapsulation process;

[0078] 4) After the microencapsulation reaction is completed, the unreacted raw materials and solvent are removed through the steps of centrifugation, washing and drying to obtain the microencapsulated anti-aging agent.

[0079] Preparation Example 8

[0080] A microencapsulated anti-aging agent, the preparation method of which is as follows:

[0081] 1) Disperse 15 kg of antioxidant in water; the antioxidant is a benzoyl diformyl UV absorber and a hindered amine light stabilizer in a weight ratio of 1:2;

[0082] 2) Mix the anti-aging agent dispersion with 18 kg of polyether diol, then add 0.5 kg of emulsifier, and disperse by shearing to form a stable emulsion with a droplet size of 500 μm;

[0083] 3) Add 0.2 kg of amine compound curing agent into the emulsion to react and complete the microencapsulation process;

[0084] 4) After the microencapsulation reaction is completed, the unreacted raw materials and solvent are removed through the steps of centrifugation, washing and drying to obtain the microencapsulated anti-aging agent.

[0085] Preparation Example 9

[0086] Different from Preparation Example 4, the anti-aging agent in Preparation Example 9 is a benzoyl diformyl ultraviolet absorber and a hindered amine light stabilizer in a weight ratio of 1:4.

[0087] Preparation Example 10

[0088] Different from Preparation Example 4, the anti-aging agent in Preparation Example 10 is a benzoyl diformyl ultraviolet absorber and a hindered amine light stabilizer in a weight ratio of 3:1.

[0089] Preparation Example 11

[0090] A microencapsulated anti-aging agent, the preparation method of which is as follows:

[0091] 1) Heat 15 kg of antioxidant to a molten state; the antioxidant is a benzoyl diformyl ultraviolet absorber and a hindered amine light stabilizer in a weight ratio of 1:2;

[0092] 2) Dissolve 3 kg of starch in water, heat and stir to form a uniform starch solution with a concentration of 15% w / v; disperse 1 kg of nano-titanium dioxide with a particle size of 200 nm in the starch solution;

[0093] 3) Add the molten antioxidant and 15 kg of polyether diol to the starch solution, then add 0.5 kg of emulsifier, and disperse by shearing to form a stable emulsion with a droplet size of 500 μm;

[0094] 4) Add 0.2 kg of amine compound curing agent into the emulsion to react and complete the microencapsulation process;

[0095] 5) After the microencapsulation reaction is completed, the unreacted raw materials and solvent are removed through the steps of centrifugation, washing and drying to obtain a microencapsulated anti-aging agent.

[0096] Preparation Example 12

[0097] Different from Preparation Example 11, the amount of nano titanium dioxide in Preparation Example 12 is 0.6 kg.

[0098] Preparation Example 13

[0099] The difference from Preparation Example 11 is that the amount of nano titanium dioxide in Preparation Example 13 is 1.5 kg.

[0100] Example

[0101] Examples 1-3

[0102] A flat-plate solar collector thermal insulation material, the preparation method of which is as follows:

[0103] S1. The phenolic resin, the blowing agent, the stabilizer and the microencapsulated anti-aging agent are mixed according to the ratio in Table 1 to obtain a mixture;

[0104] S2. adding a curing agent to the mixture and mixing to obtain a reaction system;

[0105] S3. The reaction system was heated to 60°C for pre-foaming for 35 min;

[0106] S4. After pre-foaming, pour it into a preheated mold, foam and cure it at 95°C for 1.5 hours, then cool and demould to obtain a flat-plate solar collector insulation material.

[0107] Table 1 Raw material ratio table of Examples 1-3 (kg)

[0108]

[0109] Wherein, the phenolic resin comes from Preparation Example 1; and the microencapsulated anti-aging agent comes from Preparation Example 4.

[0110] Embodiment 4-5

[0111] Different from Example 2, the phenolic resins in Examples 4-5 come from Preparation Examples 2-3, respectively.

[0112] Embodiment 6-7

[0113] Different from Example 2, the microencapsulated anti-aging agents in Examples 6-7 are from Preparation Examples 5-6, respectively.

[0114] Examples 8-12

[0115] Different from Example 2, the microencapsulated anti-aging agents in Examples 8-12 are from Preparation Examples 9-13, respectively.

[0116] Comparative Example

[0117] Comparative Example 1

[0118] The difference from Example 1 is that the microencapsulated anti-aging agent in Comparative Example 1 comes from Preparation Example 7.

[0119] Comparative Example 2

[0120] Different from Example 1, the microencapsulated anti-aging agent in Comparative Example 2 comes from Preparation Example 8.

[0121] Comparative Example 3

[0122] The difference from Example 1 is that in Comparative Example 1, the microencapsulated anti-aging agent is replaced by an equal amount of a benzoyl dicarboxylate ultraviolet absorber and a hindered amine light stabilizer in a weight ratio of 1:2.

[0123] Performance Testing

[0124] The thermal conductivity of the thermal insulation materials obtained in the examples and comparative examples was measured, and the test results are shown in Table 2.

[0125] Aging resistance test: firstly, the tensile strength and elongation at break of the thermal insulation materials obtained in the embodiments and comparative examples were measured, and then, referring to the "Plastic Laboratory Light Source Exposure Test Method Part 3: Fluorescent UV Lamp" GB-T16422.3-2022, a combination of four UV lamps was used for UV aging. After aging for 15 days, the tensile strength and elongation at break were tested again, and the aging retention rate was calculated:

[0126] Tensile strength aging retention rate = tensile strength after aging / tensile strength before aging × 100%;

[0127] Breaking strength aging retention rate = breaking strength after aging / breaking strength before aging × 100%.

[0128] Table 2 Performance test results

[0129]

[0130] Combining Examples 1-12 with Comparative Examples 1-3 and Table 2, it can be seen that the thermal conductivity of the thermal insulation material obtained in Examples 1-12 is not much different from that of Comparative Examples 1-3, indicating that the thermal insulation materials obtained in the Examples and Comparative Examples have good thermal insulation performance. However, after 15 days of ultraviolet aging treatment, the tensile strength retention rate and the breaking strength retention rate of the thermal insulation material obtained in Examples 1-12 are better than those of Comparative Examples 1-3, which indicates that the thermal insulation material obtained in the present application has excellent anti-aging performance and can be applied to flat-plate solar collectors to play a long-term thermal insulation role.

[0131] Combining Example 2 with Comparative Examples 1-3 and Table 2, it can be seen that the thermal insulation material in Example 1 has better tensile strength retention and fracture strength retention after 15 days of ultraviolet aging treatment than Comparative Examples 1-3, and the thermal insulation material in Comparative Examples 1-2 has better tensile strength retention and fracture strength retention after 15 days of ultraviolet aging treatment than Comparative Example 3. This shows that microencapsulation of anti-aging agents can greatly improve the anti-aging performance of thermal insulation materials. Among them, the anti-aging effect of using starch and polyether diol as microcapsule wall materials is better than that of single wall materials.

[0132] Combining Example 2 with Examples 6-7 and Table 2, it can be seen that the ratio of starch to polyether diol in the microcapsule wall material affects the anti-aging performance of the thermal insulation material, among which the ratio in Example 2 is better.

[0133] Combining Example 2 with Examples 10-12 and Table 2, it can be seen that after 15 days of ultraviolet aging treatment, the tensile strength retention rate and the breaking strength retention rate of the thermal insulation materials in Examples 10-12 are better than those in Example 2, which shows that adding nano-titanium dioxide to the microcapsule wall material can further improve the anti-aging properties of the thermal insulation material. This may be because the nano-titanium dioxide is embedded in the wall material, which, on the one hand, improves the surface roughness of the microcapsules and improves the bonding ability of the microcapsules with the matrix; on the other hand, the nano-titanium dioxide also has an anti-aging effect, so that the microcapsule wall material also has a certain anti-aging ability, further improving the anti-aging properties of the thermal insulation material.

[0134] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A flat-plate solar collector insulation material, characterized in that: The method comprises the following raw materials in parts by weight: 100-150 parts of phenolic resin, 10-15 parts of foaming agent, 20-25 parts of curing agent, 5-8 parts of stabilizer, and 4-8 parts of microencapsulated anti-aging agent; The microencapsulated anti-aging agent is prepared by mixing polyether diol and starch as the wall material and the anti-aging agent as the core material; The weight ratio of polyether diol to starch in the wall material is (5-8):1; The anti-aging agent is a benzoyl diformyl ultraviolet absorber and a hindered amine light stabilizer in a weight ratio of 1: (2-4).

2. A flat-plate solar collector thermal insulation material according to claim 1, characterized in that: The preparation method of the microencapsulated anti-aging agent is: 1) Heat the antioxidant to a molten state; 2) Dissolve starch in water, heat and stir to form a uniform starch solution; 3) Add the molten antioxidant and polyether diol to the starch solution, then add the emulsifier, and disperse by shearing to form a stable emulsion; 4) Add curing agent to the emulsion to react and complete the microencapsulation process; 5) After the microencapsulation reaction is completed, the unreacted raw materials and solvent are removed by centrifugation, washing and drying to obtain a microencapsulated anti-aging agent.

3. A flat-plate solar collector thermal insulation material according to claim 2, characterized in that: The particle size of the emulsion is 500-700 μm.

4. A flat-plate solar collector thermal insulation material according to claim 2, characterized in that: The wall material also includes nano titanium dioxide, which is dispersed in the starch solution.

5. A flat-plate solar collector thermal insulation material according to claim 4, characterized in that: The weight ratio of the nano titanium dioxide to the starch is 1:(2-4).

6. The flat-plate solar collector thermal insulation material according to claim 1, characterized in that: The phenolic resin is a lignin-modified phenolic resin.

7. A flat-plate solar collector thermal insulation material according to claim 6, characterized in that: The preparation method of the lignin modified phenolic resin is: a) Degradation of lignin by microwave digestion; b) melting phenol; c) mixing the degraded lignin with melted phenol at a weight ratio of 2:(3-5) to obtain a mixed solution; d) adding formaldehyde to the mixed solution in batches and reacting at 60-80°C; e) After the reaction is completed, water is removed by rotary evaporation to obtain pure phenolic resin.

8. A method for preparing the flat-plate solar collector thermal insulation material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. The phenolic resin, the blowing agent, the stabilizer and the microencapsulated anti-aging agent are mixed according to the ratio to obtain a mixture; S2. adding a curing agent to the mixture and mixing to obtain a reaction system; S3. The reaction system is heated to 50-70°C for pre-foaming for 30-40 minutes; S4. After pre-foaming, pour it into a preheated mold, foam and cure it at 90-100°C for 1-2 hours, then cool and demould to obtain a flat-plate solar collector insulation material.

Citation Information

Patent Citations

  • Phenolic foam thermal insulation material used for flat-plate solar collector

    CN107778766A

  • Agent for improving light durability of organic ultraviolet absorber

    JP2018076283A